School reform proposals : the research evidence - Molnar, Alex (Emerald Publishing Limited : Information Age Pub., 2002)
An examination of the research relating to school reform proposals. It features essays covering: early childhood education; class-size reduction in grades K-3; small schools; grouping students for instruction; public schools and their communities; teacher characteristics; and more.
Keywords: School improvement programs -- United States.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy.; elektronické knihy; electronic books